2020
DOI: 10.1371/journal.pone.0235018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome expression analysis in susceptible and resistant potato (Solanum tuberosum) cultivars to common scab (Streptomyces scabies) revealed immune priming responses in the incompatible interaction

Abstract: Common scab disease in potato has become a widespread issue in major potato production areas, leading to increasing economic losses. Varietal resistance is seen as a viable and long-term scab management strategy. However, the genes and mechanisms of varietal resistance are unknown. In the current study, a comparative RNA transcriptome sequencing and differential gene signaling and priming sensitization studies were conducted in two potato cultivars that differ by their response to common scab ( Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…For instance, increased resistance to common scab could be due to enhanced or constitutive activation of defense- or stress-related pathways especially in tubers. Recent work using transcriptomic analysis that compared gene expression between common scab resistant and susceptible potato cultivars has revealed that immune priming may indeed be involved in the induced resistance in the common scab resistant cultivar Hindenburg [ 37 ]. However, there is wide evidence that the activation of defense mechanisms is a high energy demanding process that can lead to reduction in plant growth (rev.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increased resistance to common scab could be due to enhanced or constitutive activation of defense- or stress-related pathways especially in tubers. Recent work using transcriptomic analysis that compared gene expression between common scab resistant and susceptible potato cultivars has revealed that immune priming may indeed be involved in the induced resistance in the common scab resistant cultivar Hindenburg [ 37 ]. However, there is wide evidence that the activation of defense mechanisms is a high energy demanding process that can lead to reduction in plant growth (rev.…”
Section: Discussionmentioning
confidence: 99%
“…Although the list of candidate genes is still hypothetical, several transcripts encoding related protein isoforms (e.g. MYB, WRKY, LRR receptor-like serine/threonine-protein kinase) were found to be differentially expressed between the resistant 'Hindenburg' and susceptible 'Green Mountain' cultivars inoculated with S. scabies (Fofana et al, 2020). Here, we detected a single QTL consistently in two out of three environments, that explains up to 30% of the variation for lesion index.…”
Section: Discussionmentioning
confidence: 72%
“…It was expected that Arthrobacter would break down the aromatic compound when contaminated with toluene. The Streptomyces scabiei attend the steroid degradation pathway [39]. Bradyrhizobium japonicum was reported as toluene degrader [40].…”
Section: Microbial Community Analysis In Field Soilmentioning
confidence: 99%